Pengaruh Brand Trust dan Kualitas Produk terhadap Loyalitas Konsumen dengan Brand Image Sebagai Variabel Mediasi pada Produk The Originote : Studi Kasus pada Konsumen The Originote di Amalia Beauty Store Kendal - Lilla Nanda Aprita; Henry Casandra Gultom; Mochamad Fadjar Dharmaputra (Lembaga Pengembangan Kinerja Dosen, 2025)
The Originote is a local skincare brand that has rapidly expanded in the Indonesian market, especially among young consumers seeking affordable yet effective beauty products. The brand has successfully captured public attention through continuous product innovation, minimalist packaging, and effective branding strategies that leverage social media and influencer marketing. However, despite this rapid growth, The Originote faces significant challenges related to consumer trust, particularly due to emerging negative issues surrounding the accuracy of product ingredient claims. These controversies have raised questions about product transparency and may potentially affect customer loyalty in the long term. This study aims to analyze the influence of brand trust and product quality on consumer loyalty, with brand image serving as a mediating variable. The research focuses on consumer perceptions of The Originote, specifically those who shop at Amalia Beauty Store in Kendal. A quantitative research approach was used, with purposive sampling to select 97 respondents who are known users of The Originote products. Data were collected through a structured questionnaire and analyzed using Smart-PLS 4 software for Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that brand trust has a positive and significant effect on consumer loyalty. However, surprisingly, brand trust does not significantly influence brand image, and neither brand image nor product quality has a direct significant impact on consumer loyalty. Furthermore, brand image does not mediate the relationship between brand trust, product quality, and consumer loyalty. These findings suggest that while trust remains a critical factor in fostering loyalty, other elements—possibly including emotional attachment, personal values, or customer experience—may also play a significant role. The study offers useful insights for marketers seeking to strengthen long-term relationships with consumers in a highly competitive skincare industry.